SINTESIS DAN KARAKTERISASI SILIKA GEL DARI LIMBAH KACA SERTA APLIKASINYA PADA KROMATOGRAFI KOLOM - Verry Andre Fabiani; Nelly Wahyuni; Ridho Brilliantoro; Mellisa Nurul Safitri (Tanjungpura University, 2018)
Silica gel synthesis from glass waste have been carried out with activation and purification method by using hydrochloride acid. Hydrochloride acid were varied 8 N, 10 N, and 12 N to observe optimum concentration in purification of silica gel and component separation in chromatography column. Gravimetric analysis result showed 12 N hydrochloride acid produce 100 % silica. XRD and FTIR analysis revealed that synthetic gel silica was amorphous where its IR absorption bands were at 3426 cm-1, 1620 cm-1, 1080 cm-1, 772 cm-1 and 478 cm-1. The absorption bands agreed to standard gel silica and spectrum. The most effective HCl in gel silica synthesis was 12 N, caused by its ability to separate color component in a column. The synthetic silica that can be applied as stationary phase in column chromatography.